An Analysis of Indonesia’s Free and Active COVID-19 Vaccine Diplomacy - Wicaksono, Raden Mas Try Ananto Djoko; Hirawan, Fajar Bambang; Ragamustari, Safendrri Komara (Jurnal Hubungan Internasional, 2022)
Amid a global rush for vaccines, Indonesia has had to compete with other countries to secure vaccines to protect its people from the infection of COVID-19. For its survival, Indonesia's vaccine diplomacy deemed it necessary to remain strategically neutral to prevent Indonesia from being one side of global power. The question in this research is how Indonesia’s effort to procure COVID-19 vaccine while maintaining ‘Free and Active’ foreign policy in bilateral, regional and multilateral and why ‘Free and Active’ foreign policy became important for Indonesia in conducting vaccine diplomacy. The study's aims to examine Indonesia's effort to procure COVID-19 vaccine while maintaining free and active principles and analyze the importance of free and active vaccine diplomacy to ensure the country's independence. This study uses qualitative study methods in research design with data collection techniques from primary (official reports and government records) and secondary data (books, journals, and online media). The research shows Indonesia's effort to procure the COVID-19 vaccine in three ways, namely bilateral (Australia, China, Russia, UK, and the US), regional (ASEAN and IORA), and multilateral (UN and Covax-AMC EG) cooperation with six types of vaccines has secure in Indonesia. China readily supported Indonesia in turning into a vaccine manufacturing hub for Southeast Asia. In this regard, the pandemic would possibly, facilitate Jakarta's nearer ties with Beijing. Thus, free and active foreign policy becomes important for Indonesia in vaccine diplomacy because it balances the national interest.